Wave energy extraction for an array of dual-oscillating wave surge converter with different layouts. (15th June 2021) - Cheng, Yong; Xi, Chen; Dai, Saishuai; Ji, Chunyan; Cocard, Margot
Graphical abstract: Figure. Coordinate system and sketch of oblique waves interact with an array OWSC system, the motivation of this paper is to assess energy extraction of an array of dual-OWSC system with different layout schemes in comparison with an isolated OWSC, which can be regarded as a guideline for multi-array configuration in realistic wave farm. Prevised studies have primarily focused on the influence of a specified size and layout of OWSCs on the energy extraction performance using linear wave theory. The motivation and novelty of this paper is twofold; firstly to develop an accurate time-domain three-dimensional (3-D) hydrodynamic model to optimize the design and configuration of a front-back array of dual-OWSC system, and secondly to compare the energy extraction performance of an front-back array system, an in-line array system and a staggered array system. This will help lead to efficiency-enhancing multi-array configuration in realistic wave farm, which broadens the effective bandwidth of energy extraction. Highlights: The hydrodynamic behaviors of different array of dual-OWSC systems are compared. An accurate approach is developed to obtain optimum layout and PTO coefficients. Wave resonance in a wide gap can enhance energy extraction in large wave periods. An in-line array and a staggered array cover different effective bandwidth, respectively. Oblique waves lead to stronger disturbance of free surface between flap sides. Abstract: Array configuration of oscillating wave surge converter (OWSC) devices in nearshore is a preferable option for realizing a cost-balance of extracting wave energy and reducing installation expense due to closer installed place to coastline. The goal of the present work is to assess energy extraction of an array of dual-OWSC system with different layout schemes in comparison with an isolated OWSC, which can be regarded as a guideline for multi-array configuration in realistic wave farm. The coupled three-dimensional (3-D) hydrodynamic model is established based on the potential flow theory with fully nonlinear boundary condition in time domain. A non-dimensional approach is conducted to focusing on the accurate effects of multi-body interaction, wave nonlinearity, wave resonance, mechanical damping, layout scheme and oblique incidence as optimization design. For a front-back array system, wave resonance in dual-module gap enhances significantly the energy extraction of the front OWSC but does not contribute much to that of the back OWSC. Furthermore, wave resonance in wide gap has a positive effect on the capture efficiency in large wave periods. An in-line array system has a beneficial performance in small wave periods, while a staggered array system realizes more energy extraction in resonance region. A strong wave disturbance between flap sides of an in-line and staggered system, leads to the increase of energy extraction for the back OWSC with imposing small incident wave heading. Therefore, the combination of multi-triple-array OWSC with different gap distances will provide a desirable configuration which is independent on oblique wave conditions.